Analisis Faktor yang Memengaruhi Nilai Perusahaan dengan Kebijakan Utang Sebagai Variabel Intervening Pada Sektor Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia - Cindhi Hesti Yana; R.A. Norromadani Yuniati; Arfiana Dewi (Proceeding Maritime Business Management Conference, 2023)
The main goal of the company is to increase the value of the company in the long term. Firm value is interpreted as an investor's view of the company's level of success in managing company resources. This research was conducted to analyze the effect of profitability, free cash flow and firm size on firm value with debt policy as an intervening variable. The p opulation in this study is the transportation and logistics sector companies listed on the Indonesia Stock Exchange using purpove sampling. The samples used in this study were 17 companies. The method for examining the influence between variables is to test panel data regression analysis and path analysis. The results of this study indicate that profitability and debt policy have an effect on firm value, because the greater the profitability and debt policy values, the greater the firm value, while free cash flow and firm size have no effect on firm value. Profitability has an effect on debt policy, because the higher the profitability, the lower the debt policy, while free cash flow and size have no effect on debt policy. The intervening variable of debt policy cannot mediate the influence between profitability on debt policy. Companies in the transportation and logistics sector need to increase free cash flow and optimize the number of assets so that they can attract investors' attention regarding investment decisions that can indicate an increase in company value.